Identifikasi Komponen Produk Pariwisata 4A dan Kendala Pengembangan Desa Balun Sebagai Desa Wisata Pancasila di Kabupaten Lamongan, Jawa Timur - Indrawati, Veni; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2024)
Balun village, widely recognized as a Pancasila village, boasts considerable tourism potential due to its exceptional and harmonious religious diversity. The village is distinguished by its residents, who practice Islam, Christianity, and Hinduism in close proximity, fostering a rich and dynamic cultural and religious landscape. Key attractions include the Miftahul Huda Mosque, a prominent site for the Muslim community; Jawi Wetan Christian Church, which serves as a center for Christian worship; Sweta Maha Suci Temple, a revered Hindu site; and the historic Mbah Alun Tomb, a significant cultural landmark. Additionally, the Pancasila monument in the village stands as a symbol of unity and tolerance among its diverse religious groups. Despite these advantages, Balun village has yet to fully harness its tourism potential. The village’s development is impeded by several factors, including a general lack of awareness among local residents about the benefits that tourism could bring to their community, both economically and culturally. Financial constraints further exacerbate the issue, limiting the ability to invest in necessary infrastructure and promotional activities. Additionally, there is a noticeable deficit in effective collaboration between local stakeholders, including government bodies, community leaders, and the tourism industry, which is crucial for cohesive and sustainable tourism development. This research aims to conduct a thorough analysis of these barriers, assessing their effects on the tourism growth in Balun village. By delving into these challenges, the study will highlight the village’s role as a crucial symbol of tolerance and cultural diversity within the Lamongan district. It will also offer strategic recommendations to address these issues, with the goal of enhancing tourism growth and positioning Balun village as a leading example of religious harmony and cultural richness. Ultimately, the research seeks to improve the village's attractiveness as a distinctive and inclusive tourist destination, benefiting both the local community and visitors. Keywords: Development, Tourism Potential, Religious Diversity, Harmony and Tolerance, Tourism Constraints